Cannabidiol-Loaded Mixed Polymeric Micelles of Chitosan/Poly(Vinyl Alcohol) and Poly(Methyl Methacrylate) for Trans-Corneal Delivery - Alejandro Sosnik; Ronya Ben Shabo; Hen Moshe Halamish (MDPI AG, 2021)
Ocular drug delivery is challenging due to the very short drug residence time and low permeability. In this work, we produce and characterize mucoadhesive mixed polymeric micelles (PMs) made of chitosan (CS) and poly(vinyl alcohol) backbones graft-hydrophobized with short poly(methyl methacrylate) blocks and use them to encapsulate cannabidiol (CBD), an anti-inflammatory cannabinoid. CBD-loaded mixed PMs are physically stabilized by ionotropic crosslinking of the CS domains with sodium tripolyphoshate and spray-drying. These mixed PMs display CBD loading capacity of 20% w/w and sizes of 100-200 nm, and spherical morphology (cryogenic-transmission electron microscopy). The good compatibility of the unloaded and CBD-loaded PMs is assessed in a human corneal epithelial cell line. Then, we confirm the permeability of CBD-free PMs and nanoencapsulated CBD in human corneal epithelial cell monolayers under liquid-liquid and air-liquid conditions. Overall, our results highlight the potential of these polymeric nanocarriers for ocular drug delivery.